The importance of primary surgery in patients with de novo stage IV BC surviving at least 5 years: Protocol MF07-01 randomized clinical trial - Ozmen, V.; Ozbas, S.; Karanlik, H.; Muslumanoglu, M.; Igci, A.; Canturk, Z.; Utkan, Z.; Ozaslan, C.; Evrensel, T.; Uras, C.; Aksaz, E.; Soyder, A.; et al. (OXFORD UNIV PRESS, 2019)
44th Congress of the European-Society-for-Medical-Oncology (ESMO), Barcelona, SPAIN, SEP 27-OCT 01, 2019